“Pre-Treatment“ and “Post-Treatment” Systemic Inflammatory Markers: Is There Any Prognostic Role for Metastatic Cervical Cancer on Bevacizumab Containing Treatment? - Serkan Yaşar; Ahmet Kadıoğlu; Arif Akyildiz; Nadiye Sever; Mehmet Emin Büyükbayram; Mehmet Bilici; Elanur Karaman; Mehmet Uzun; Murat Bardakcı; Caglar Koseoglu; Irem Bilgetekin; Mehmet Cihan İçli; et al. (Medicina)
Background and Objectives: Despite developments in cervical cancer (CC) treatment, an advanced stage is a poor prognostic factor. Cervical cancer is an immunogenic tumor in which viruses, like HPV, play a role in carcinogenesis. Therefore, systemic inflammatory markers (SIMs) may have prognostic value. Most studies on SIMs focus on the early stage by evaluating pretreatment levels. This study aims to evaluate the prognostic and predictive values of both pretreatment and post-treatment parameters at the advanced stage, as well as treatment efficacy after progression with first-line treatment. Materials and Methods: A total of 133 advanced-stage CC patients with progression on first-line platin–paclitaxel and bevacizumab were evaluated retrospectively. Demographic and histopathological characteristics were recorded along with treatment details. Pre-treatment baseline blood parameters and post-treatment follow-up values were recorded to calculate SIMs as the neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), systemic immune-inflammation index (SII), and systemic inflammatory response index (SIRI). Results: Median values for SIMs were accepted as cut-off values. Post-treatment values demonstrated stronger predictive power, with pre-treatment SIRI and NLR being significant only in univariate analysis, but not in multivariate analysis. High post-treatment SIRI (>2.1) was correlated with shorter overall survival (OS) and considered a poor prognostic factor. High post-treatment SIRI (>2.1), -SII (>746), and -PLR (>197) emerged as independent prognostic factors for progression-free survival (PFS). Their prognostic values were clearer in the whole population and the metachronous metastatic subgroup. Rechallenge of platinum-based chemotherapy was an option for those who had at least 6 months of PFS with first-line platinum-based chemotherapy. Bevacizumab addition to single-agent or combination regimens led to improved ORR as well. Conclusions: Post-treatment SIRI is a promising prognostic factor for OS, while post-treatment SIRI, SII, and PLR may serve as convenient SIMs for PFS. Platinum-based combination chemotherapy reinduction is a feasible second-line treatment strategy, especially with the addition of bevacizumab.